A comparison of classifiers applied to the problem of biopsy images analysis - Hlavcheva, Daria; Yaloveha, Vladyslav; Podorozhniak, Andrii; Lukova-Chuiko, Nataliia (Національний технічний університет "Харківський політехнічний інститут", 2020)
The purpose of the research is to compare classification algorithms for the histopathological images analyzing issue and to optimize the parameters for obtaining better classification accuracy. The following tasks are solved in the article: preprocessing of BreCaHAD dataset images, implementation and training of CNN, applying K-nearest neighbours, SVM, Random Forest,XGBoost, and perceptron algorithms for classifying features that were extracted by CNN, and results comparison. The object of the research is the process of classifying tumor cells in the microscopic biopsy images. The subject of the research is the processof using ML algorithms for classification of the features extracted by CNN from input biopsy image. The scientific novelty of the research is a comparative analysis of classifiers on the task of “tumor” and “healthy” cells images classification from processed BreCaHAD dataset. As a result it was obtained that from chosen classifiers SVM reached the highest accuracy on test data –0.972. This is the only algorithm that shows better accuracy than perceptron. Perceptron gets 0.966 classification accuracy. K-nearest neighbours, Random Forest, and XGBoost algorithms reached lower results. The algorithms' hyperparameters optimization was carried out. The results have been compared with related works. The following research methodsare used: the theory of deep learning, mathematical statistics, parameters optimization.

Мета дослідження - порівняння алгоритмів класифікації для аналізу гістопатологічних зображень і оптимізація гіперпараметрів алгоритмів класифікації для збільшення результуючої точності. У статті вирішуються наступні завдання: попередньо обробленого набору даних BreCaHAD, реалізація та навчання CNN, застосування алгоритмів K-найближчих сусідів, SVM,Random Forest, XGBoost і персептрона для класифікації ознак, отриманих CNN, і порівняння результатів. Об'єктом дослідженняє процес класифікації пухлинних клітин на знімках мікроскопічної біопсії. Предметом дослідження є процес використання алгоритмів машинного навчання для класифікації ознак, отриманих CNN з вхідного зображення біопсії. Наукова новизна дослідження - порівняльний аналіз класифікаторів на завданні класифікації зображень «пухлинних» і «здорових» клітин з предобработанного набору даних BreCaHAD. В результаті було отримано, що з обраних класифікаторів SVM має найбільшу точність на тестовій вибірці - 0,972. Це єдиний алгоритм, який отримав більшу точність, ніж персептрон. Точність класифікації персептрона на тестовій вибірці склала 0,966. K-найближчі сусіди, алгоритми Random Forest і XGBoost в результаті експериментів показали меншу точність. Проведена оптимізація гіперпараметрів алгоритмів. Результати були зіставлені з подібними роботами. Були використані такі методи дослідження: теорія глибокого навчання, математична статистика, оптимізація параметрів.
Порівняння класифікаторів, у застосуванні до проблеми аналізу знімків біопсії
Keywords: machine learning; deep learning; convolutional neural network; grid search; машинне навчання; глибоке навчання; згорткова нейронна мережа; пошук по сітці